5-Methyl-1H-Benzotriazole as an Effective Corrosion Inhibitor for Ultra-Precision Chemical Mechanical Polishing of Bearing Steel. Issue 13 (16th September 2020) - Liu, Jinwei; Jiang, Liang; Wu, Hanqiang; Zhao, Ting; Qian, Linmao
Abstract : 5-methyl-1H-benzotriazole was used as an effective corrosion inhibitor in acidic H2 O2 -based slurries for ultra-precision chemical mechanical polishing (CMP) of a high carbon chromium GCr15 bearing steel (AISI 52100). The CMP performance of GCr15 steel and the corresponding corrosion inhibition mechanism of 5-methyl-BTA were thoroughly investigated. The CMP results reveal that, compared with 1, 2, 4-triazole, 1, 2, 3-triazole and BTA, 5-methyl-BTA achieves the best corrosion inhibition performance, and the surface roughness R a of GCr15 steel greatly improves, which can be attributed to the triazole and hydrophobic methyl functional groups. In synergy with H2 O2, 5-methyl-BTA can be both chemically and physically adsorbed on the GCr15 steel surface in acidic medium. Specifically, the chemical adsorption mainly occurs by chemical reactions between 5-methyl-BTA and iron of GCr15 steel to form a surface complex. In the presence of 1.0 wt% H2 O2 and 20 mM 5-methyl-BTA, the sparse corrosion inhibition film formed by 5-methyl-BTA together with the dense oxide film constitutes a complete passivation film, eventually resulting in the nanoscale planarization. The results can provide a guide for the selection of appropriate nitrogen-containing corrosion inhibitors for bearing steels CMP.